Adaptive toolkit of branch-oriented workshop environment for enlargement the cloud-based e-learning media platform - Tetyana V. Neroda; Lidia V. Slipchyshyn; Ivan O. Muzyka (Academy of Cognitive and Natural Sciences, 2021)
The ways of providing comprehensive efficiency increase in communication facilities of the academic space are given with regard to stipulated methods of managing distributed network resources. Selected the user interfaces types are distinguished according to user actions in the studied subject area, which made it possible to justify and hierarchically organize the categories of adaptive toolkit of the branch-oriented workshop environment by the classes of components declared in the project, which are closely related to the scheme of learning experiment and are basic means for simulating transients. The analytical models of classes of components of the virtual laboratory stand are compiled, the elements of which represent the properties and methods for visualization and further processing of interacting instances of the basic locations of the subject area, while ensuring system stability and controllability by clear distribution of functionality. Finally, the unification of component set template properties of the subject area is implemented, which greatly extending the targeted destination of virtual platform and increasing number of educational disciplines of academic course covered by the designed media resource. The results of the pedagogical verification showed an increase in the students' performance in mastering the subject area by means of presented branch-oriented workshop environment.